2018
DOI: 10.1177/1358863x18768685
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization metrics associated with hospital-level variation in inferior vena cava filter utilization for patients with venous thromboembolism in the United States: Implications for quality of care

Abstract: Variation in the use of inferior vena cava filters (IVCFs) across hospitals has been observed, suggesting differences in quality of care. Hospitalization metrics associated with venous thromboembolism (VTE) patients have not been compared based on IVCF utilization rates using a national sample. We conducted a descriptive retrospective study using the Nationwide Readmissions Database (NRD) to delineate the variability of hospitalization metrics across the hospital quartiles of IVCF utilization for VTE patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
1
Order By: Relevance
“…In that same study, Black patients were also less likely to receive an intervention of any kind, even after stratifying by PE severity. In addition to patient characteristics associated with IVCF use, previous studies have shown significant variation in IVCF placement at the hospital level [16,29]. Although we did not find significant differences by race and facility ACO status, variations in IVCF placement and retrieval by the site of VTE service were observed, suggesting that facility practices and characteristics may play a role in the use of IVCFs.…”
Section: Discussioncontrasting
confidence: 78%
“…In that same study, Black patients were also less likely to receive an intervention of any kind, even after stratifying by PE severity. In addition to patient characteristics associated with IVCF use, previous studies have shown significant variation in IVCF placement at the hospital level [16,29]. Although we did not find significant differences by race and facility ACO status, variations in IVCF placement and retrieval by the site of VTE service were observed, suggesting that facility practices and characteristics may play a role in the use of IVCFs.…”
Section: Discussioncontrasting
confidence: 78%